2011
DOI: 10.4088/jcp.10m06130gry
|View full text |Cite
|
Sign up to set email alerts
|

Brief Behavioral Therapy for Refractory Insomnia in Residual Depression

Abstract: clinicaltrials.gov Identifier: NCT00610259.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 0 publications
8
89
2
1
Order By: Relevance
“…Behind these assumptions, we speculated that improvement in QoL was better explained by changes in * * * depression severity, and that a time lag might exist between improvements in insomnia or depression and improvements in QoL. However, considering the results of the present study and of our previous study on insomnia and depression outcomes, 16 it now seems more likely that insomnia, depression and QoL almost simultaneously improve to a normal range when a patient responds successfully to treatment. Although the findings of this study are very promising, there were some methodological limitations.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Behind these assumptions, we speculated that improvement in QoL was better explained by changes in * * * depression severity, and that a time lag might exist between improvements in insomnia or depression and improvements in QoL. However, considering the results of the present study and of our previous study on insomnia and depression outcomes, 16 it now seems more likely that insomnia, depression and QoL almost simultaneously improve to a normal range when a patient responds successfully to treatment. Although the findings of this study are very promising, there were some methodological limitations.…”
Section: Discussioncontrasting
confidence: 51%
“…13,14 As for psychotherapy, several previous trials including ours have confirmed the efficacy of CBT-I in insomnia in depression. 15,16 However, to the best of our knowledge, no previous trials on psychotherapy for insomnia in depression have reported QoL outcomes, and which aspects of QoL can be changed by psychotherapy are as yet unknown. Moreover, even if QoL outcomes were found to be improved after psychotherapy, questions would still remain as to whether improvement in insomnia or improvement in depression led to better QoL.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 3 more Smart Citations